2022
DOI: 10.1002/adma.202205153
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Hollow Phenolic Resin Nanoreactors with Precise Metal Nanoparticles Spatial Location toward Promising Heterogeneous Hydrogenations

Abstract: Hollow nanostructures with fascinating properties have inspired numerous interests in broad research fields. Cell‐mimicking complex hollow architectures with precise active components distributions are particularly important, while their synthesis remains highly challenging. Herein, a “top‐down” chemical surgery strategy is introduced to engrave the 3‐aminophenol formaldehyde resin (APF) spheres at nanoscale. Undergoing the cleavage of (Ar)CN bonds with ethanol as chemical scissors and subsequent repolymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The peak of methylene ether bridge vibration at 1120 cm –1 could also be observed , (Figure i). Hence, similar to the typical phenol-aldehyde condensation, it also could be concluded that OPC would react with formaldehyde to form a hydroxymethyl phenol structure under alkaline and 80 °C conditions first, and the resulting hydroxymethyl phenol would be further dehydrated and condensed with phenol or itself and form a methylene bridge between polyphenols, ,, resulting in gel network formation.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The peak of methylene ether bridge vibration at 1120 cm –1 could also be observed , (Figure i). Hence, similar to the typical phenol-aldehyde condensation, it also could be concluded that OPC would react with formaldehyde to form a hydroxymethyl phenol structure under alkaline and 80 °C conditions first, and the resulting hydroxymethyl phenol would be further dehydrated and condensed with phenol or itself and form a methylene bridge between polyphenols, ,, resulting in gel network formation.…”
Section: Resultsmentioning
confidence: 79%
“…Phenol-aldehyde condensation is a classical chemical reaction occurring between phenol and formaldehyde, which could afford the formation of many robust polymeric materials. , Although this strategy has been widely applied in the construction of industrial resin materials, however, limited studies have reported its application for hydrogel preparation. Theoretically, phenol-aldehyde condensation is quite suitable for fabricating polyphenolic hydrogels because it is a facial and in situ reaction, which could well address the problems faced by traditional strategies.…”
Section: Introductionmentioning
confidence: 99%
“…As a polymeric semiconductor, graphitic carbon nitride (g-C 3 N 4 ) has exhibited great potential in photocatalytic H 2 O 2 production, owing to its unique features such as visible light response ability, a proper band edge for ORR, good stability, environmental benignity, low-cost composition, and facile preparation. However, its photocatalytic activity is limited by the intrinsic disadvantages of easy recombination between photo-generated electron and hole, low selectivity toward the 2 electron (2 e – ) path, and the low reaction rate derived from the unavailable interaction between the reactant and active photo-generated electron in the ORR process. Recently, the specific void space inside a distinct shell cavity of a hollow sphere nanoreactor can be beneficial for the accumulation or confinement of reactant molecules and enhance the available interaction between reactants and active sites, resulting in the improvement of catalytic reaction dynamics. Thus, it can be deemed that the construction of a nanoreactor with a hollow structure in the g-C 3 N 4 photocatalytic system will achieve efficient production of H 2 O 2 . With this regard, it also can be expected that the acceleration of photo-generated charge separation with electron transfer from g-C 3 N 4 to its interior active sites can contribute to achieving efficient photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Recently, monodisperse colloidal carbon nanospheres are particularly attractive for stabilizing the active components due to their tunable diameter, narrow size distribution, and excellent mechanical/chemical stability. [12] However, for a great deal of the previously reported carbon nanospheres, the average diameter is generally >100 nm, [13] which suggests that, as compared with the smaller-diameter counterparts (for instance, 50 nm), the available surface area and the number of the anchored metal sites are dramatically reduced in case of the same loading mass. [14] Therefore, the precise synthesis of colloidal carbon nanospheres with small size for supporting high density of FeN 4 single sites would open up a new opportunity to maximize the metal utilization efficiency and further boost the ORR activity of Fe─N─C SACs.…”
Section: Introductionmentioning
confidence: 99%